Empowering Rural Culinary MSMEs Through Digital Literacy And Branding Strategies - Yurniwati Yurniwati; Luciana Luthan; Vima Tista Putriana; Lisa Rahayu; Ghaitsa Nashwa; Ersya Syahira; Andes Setia; Fikra Riberta (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2026)
This community service aimed to help rural culinary MSMEs strengthen their ability to use digital marketing for wider market reach and consistent branding. The program applied a participatory approach through digital literacy training, logo creation, and the use of social media and marketplace platforms. The main beneficiary was Resty Catering & Cake, located in Pesisir Selatan, Indonesia. Activities included on-site training, mentoring, and follow-up monitoring. The results were observed qualitatively and through performance indicators, such as activating two marketplace accounts, publishing promotional content, and initiating online transactions. Within two weeks, the partner recorded five online sales and recruited ten resellers, demonstrating better digital engagement and market access. The results show that digital literacy, combined with technology-based empowerment, has become the primary driver of rural business. The mentoring model introduced here combines branding and digital marketing, offering a practical approach that can be replicated for similar MSMEs to support inclusive economic growth.